1988
DOI: 10.1002/crat.2170230803
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of mechanism of agglomeration of KCl crystallization

Abstract: The article presents an analysis into agglomeration during KC1 vacuum crystallization. The theoretical and experimental investigations into the mechanism of agglomeration during mass crystallization result in an extension of the growth phenomena within the known model equations. The basis for this is essentially constituted by the collision model concepts of the theory of floculation in disperse systems. The parameters derived from the microprocess analysis (energy dissipation, content of solids, growth rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…The agglomeration of crystals was divided into three basic steps: collision, inter‐particle adhesion and simultaneous growth of agglomerates. [ 25,26 ] We speculated the agglomeration mechanism of niacin crystals based on the results above, as shown in Figure . The first stage: the niacin crystals newly formed in the stage of nucleation approach and interconnect with each other; the second stage: the contacting crystal faces form hydrogen bonding and π–π stacking by the functional groups (pyridyl and carboxyl), causing microscopic interactions between specific crystal faces and thus crystal mal‐growth (Figures 4 and 5); the third stage: with the consumption of supersaturation, the mal‐growth agglomerates in the system grow into bundle‐shape crystals (Figure 2).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The agglomeration of crystals was divided into three basic steps: collision, inter‐particle adhesion and simultaneous growth of agglomerates. [ 25,26 ] We speculated the agglomeration mechanism of niacin crystals based on the results above, as shown in Figure . The first stage: the niacin crystals newly formed in the stage of nucleation approach and interconnect with each other; the second stage: the contacting crystal faces form hydrogen bonding and π–π stacking by the functional groups (pyridyl and carboxyl), causing microscopic interactions between specific crystal faces and thus crystal mal‐growth (Figures 4 and 5); the third stage: with the consumption of supersaturation, the mal‐growth agglomerates in the system grow into bundle‐shape crystals (Figure 2).…”
Section: Resultsmentioning
confidence: 98%
“…Their results indicated that crystal agglomeration is a continuous and dynamic process that undergoes collision, adhesion, and simultaneous growth. [ 25,26 ] In this context, effectively controlling it requires determining the critical steps involved in its process.…”
Section: Introductionmentioning
confidence: 99%
“…Crystallization was modeled using a population balance model, modeling crystal growth, agglomeration, and aggregation as described in the literature [13,15,16,24] written in Equation (3). Crystal nucleation was neglected.…”
Section: Modeling Of Crystallizationmentioning
confidence: 99%
“…This work shows a model-based approach to link the evaporation and centrifugal models with a sophisticated crystallization model. For crystallization in general, modeling crystal growth and thereby crystallization end times dependent on the main influence-temperature-has widely been successful [13][14][15][16][17][18] in some cases also including agglomeration or crystal attrition. Other factors, however, such as seed crystal size, amount, or the addition of additives such as esters are likely to influence an industrial sucrose process [2].…”
Section: Introductionmentioning
confidence: 99%
“…Процесс перекристаллизации чаще всего ведет к уменьшению содержания в осадке мелкодисперсных фракций, повышению степени изометричности кристаллов [6,7]. Управление каждым из указанных процессов требует знаний особенностей их протекания и воздействия этих процессов на конечный гранулометрический состав кристаллизата [8,9].…”
Section: Patterns Of Potassium Chloride Mass Polytermic Crystallizationunclassified